ROLE OF MICROBIOLOGY AND INFLAMMATORY BIOMARKERS IN PLANNING RECONSTRUCTIVE TREATMENT OF CHRONIC WOUNDS: LITERATURE REVIEW - Milović, Jelena; Radanović, Dražen; Ćurčić, Mihajlo; Misić Mandić, Vanja; Rudić, Marija; Knežević, Saša; Giljača, Sonja (HEALTH CARE, 2026)
Chronic wounds represent a significant clinical and public health burden, with increasing prevalence among elderly and patients with diabetes and vascular diseases. Proper planning of reconstructive treatment requires a comprehensive understanding of microbiological processes and inflammatory biomarkers reflecting wound status. The aim of this study was to analyze contemporary approaches to the diagnosis and planning of reconstructive treatment of chronic wounds, emphasizing the role of microbiology and inflammatory biomarkers. Review of 18 studies published between 2010 and 2025 was presented in the paper, focusing on microbial profiles, inflammatory markers, and reconstructive treatment modalities. The most common microorganisms are Staphylococcus aureus, Pseudomonas aeruginosa, and Acinetobacter baumannii. Elevated CRP and IL-6 levels correlate with infection and poor graft outcomes, while normalization indicates readiness for reconstruction. Epidemiological data show an 8–10% annual increase in chronic wound prevalence in Europe, alongside rising bacterial resistance. Microbiological evaluation and biomarker monitoring should be integral to reconstructive planning protocols in chronic wounds. This approach improves outcome prediction, reduces postoperative complications, and promotes rational therapy use.